Nuclear Physics: Present and Future - Greiner, Walter (FIAS Interdisciplinary Science Series,, 2015)
State-of-the-art survey of topics in nuclear physics by leading practitioners in the field. Major foci are superheavy nuclei and neutron-rich exotic nuclei. In addition new developments in nuclear fission and nuclear cluster decay are shown. Finally developments in relativistic heavy ion collisions and the physics of supercritical fields are detailed.